Penerapan Arsitektur Vernakular Dalam Perancangan Kawasan Wisata Adat Kerajaan Bulutana Di Malino Gowa - Melati Indira Adininggar; Sahabuddin, Wasilah; Amin, Burhanuddin (TIMPALAJA : Architecture Student Journals, 2023)
The diversity of ethnic groups, customs and cultures, as well as natural beauty make Indonesia a country that has a lot of potential for tourist objects and attractions that are second to none compared to any other country in the world. From Sabang to Merauke along the equator from Miangas Island to Rote Island, it is integrated into the administrative area of ​​34 provinces inhabited by hundreds of ethnic groups. The tourism sector is increasingly strengthened by traditional wealth to its natural beauty. The customary area of ​​the Bulutana Kingdom has great potential for wide-open tourism development. Institutions and indigenous peoples who still exist are the main factors in developing the Bulutana Traditional Tourism Area as an established traditional environment. The design of the Indigenous Tourism Area uses a vernacular architectural approach, a vernacular architectural approach is used in the design because it can create harmony with the existing area both in terms of technique and the use of local materials. Additionally responsive to climate, site, and environment. It is hoped that the atmosphere of the past can be revived in the Bulutana Kingdom Traditional Tourism Area. So that it can become an area that is visited not only with the aim of taking a vacation but can add knowledge about culture and customs that have been lost.